The Diplomat-Scholar : A Biography of Leon Ma. Guerrero - Fernandez, Erwin Soriano (Book collections on Project MUSE., 2017)
Leon Ma. Guerrero (1915-82), a top-notch writer and diplomat, served six Philippine presidents, beginning with President Manuel L. Quezon and ending with President Ferdinand E. Marcos. In this first full-length biography, Guerrero's varied career as writer and diplomat is highlighted from an amateur student editor and associate editor of a prestigious magazine to ambassador to different countries that reflected then the exciting directions of Philippine foreign policy. But did you know that he served as public prosecutor in the notorious Nalundasan murder case, involving the future Philippine.